The effect of loading rate on the in-plane shear strength of tri-axial braided composites. (February 2022) - May, Michael; Kilchert, Sebastian
The in-plane shear strength of tri-axial braided composite materials was measured for three different braid angles (30°, 45°, and 60°) and two strain rates (0.001 s −1 ; 3 s −1 ) using the three-rail shear test. The in-plane shear strength was found to be sensitive to both—the braid angle and the strain rate. An increase of braid angle resulted in a reduction of shear strength, whilst an increase of loading rate resulted in an increase of shear strength of 8%–17%, depending on the braid angle.